The Rejection of Itsbat Nikah for an Unauthorized Polygamous Marriage: A Study of Religious Court Decision of Jombang Number 2522/Pdt.G/2023/PA.Jbg - Salma Salsabila 'Izza; Ahmad Maula Hadi; Riyan Ramdani (STAI Miftahul Ula Nganjuk, 2026)
This study aims to analyze the legal considerations of the panel of judges in Decision No. 2522/Pdt.G/2023/PA.Jbg regarding the rejection of a petition for the validation of a polygamous marriage without court permission, the legal status of polygamy permission after the dissolution of the first marriage, and the legal implications for the second wife and children. This study employs an empirical legal method with a descriptive-analytical approach. Data were collected through literature review, analysis of court decisions, and interviews with judges at the Jombang Religious Court. The results of the study indicate that the panel of judges rejected the application for itsbat nikah because, at the time the second marriage took place, the applicant was still legally married to his first wife and had not obtained a polygamy permit from the court as stipulated in positive law and Supreme Court Circular Letter (SEMA) No. 3 of 2018. The judges’ reasoning placed greater emphasis on the aspects of legal certainty and the administrative order of marriage. The rejection of the itsbat nikah has legal implications for the status of the second wife, the rights of the children, civil registration, and inheritance rights. However, the judges offered a solution in the form of a new marriage contract after the dissolution of the first marriage in order to obtain legal recognition from the state.